Flame-retardant fireproof cable material and preparation method thereof

By using low-density polyethylene resin and nylon as the matrix in the cable material, combined with a multi-step processed composite flame retardant and styrene-silicone oil copolymer, the flame retardant and aging resistance problems of the cable material are solved, and excellent mechanical properties and long-term stability are achieved.

CN120623620APending Publication Date: 2025-09-12WUXI HUANENG ELECTRIC CABLE

Patent Information

Application Number
CN202511059758.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-30
Publication Date
2025-09-12

AI Technical Summary

Technical Problem

Existing cable materials have problems such as poor flame retardancy, insufficient mechanical properties and poor aging resistance during outdoor use. In particular, the weak dispersibility and bonding strength of inorganic fillers lead to a decline in material performance.

Method used

Low-density polyethylene resin is used as the matrix material, nylon is added to improve tensile strength, and dispersibility is improved through multi-step processing of expandable graphite and composite flame retardants. Styrene-silicone oil copolymer is combined to improve the material's heat aging resistance, forming a chemical bridging structure to enhance mechanical properties.

Benefits of technology

The prepared flame-retardant and fire-proof cable material has excellent mechanical properties, flame-retardant properties and aging resistance in long-term outdoor use, ensuring structural stability and service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005525379770000141
    Figure BDA0005525379770000141
Patent Text Reader

Abstract

The invention relates to the technical field of cable materials, and particularly discloses a flame-retardant fireproof cable material and a preparation method thereof.According to the flame-retardant fireproof cable material, low-density polyethylene resin is adopted as a base material, basic electrical insulation performance and flexibility are provided, and meanwhile the machinability of the material is guaranteed; according to the flame-retardant fireproof cable material, nylon is added into the raw materials, the tensile strength of the material is improved, the technical problems that a traditional inorganic filler is poor in dispersity and prone to migration and failure are solved by conducting multi-step treatment on expansible graphite, and the prepared flame-retardant fireproof cable material has excellent mechanical performance, flame retardance and aging resistance and is suitable for industrial production. And the structural stability and the service life of the cable material in a long-term outdoor harsh environment are ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of cable materials, and in particular to a flame retardant and fireproof cable material and a preparation method thereof. Background Art

[0002] As the core carrier of power and signal transmission, the performance of cables depends largely on the properties of their insulation and sheath materials. Currently, widely used cable materials primarily include two major organic polymers: plastics and rubbers. Plastics, such as polyvinyl chloride and cross-linked polyethylene, have poor flame retardancy, while rubbers, such as ethylene propylene rubber and silicone rubber, have average flame retardancy and mechanical properties.

[0003] In the actual production process, in order to improve the flame retardant properties of cable materials, inorganic flame retardant fillers are usually added. However, there are two disadvantages in directly adding inorganic flame retardant fillers to the raw materials: first, the surface energy of the inorganic filler particles is high, and they are in a thermodynamically unstable state, and are very easy to aggregate into agglomerates, which directly affects the application effect of the inorganic filler particles; second, the surface of the inorganic filler particles is hydrophilic and oleophobic, and has strong polarity, which makes it difficult to disperse evenly in the rubber compound. The bonding force between the inorganic filler particles and the rubber compound is weak, resulting in interface defects and causing a decline in the performance of the cable material. In addition, since the cable is used outdoors for a long time and is subjected to heat, oxygen aging and ultraviolet radiation, it is easy to cause aging and degradation.

[0004] Chinese patent document CN202211179847.1 discloses a flame-retardant PVC cable material and a preparation method thereof. The PVC cable material comprises: 100-120 parts of PVC resin, 40-60 parts of plasticizer, 15-24 parts of filler, 5-15 parts of flame retardant, 5-10 parts of antioxidant, 2-4 parts of lubricant and 3-6 parts of stabilizer. The filler is modified TiO2 nanofiber and silicon nitride nanofiber. The prepared cable material has excellent flame retardant properties, but its mechanical properties, especially aging resistance, still need to be further improved. Summary of the Invention

[0005] In view of the deficiencies of the prior art, the object of the present invention is to provide a flame retardant and fireproof cable material and a preparation method thereof, wherein the prepared cable material has excellent mechanical properties, flame retardant properties and aging resistance.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A flame retardant and fireproof cable material comprises the following raw materials, calculated by weight: 80-100 parts of low-density polyethylene resin, 10-15 parts of nylon, 15-25 parts of composite flame retardant, 8-12 parts of compatibilizer, 2-4 parts of antioxidant, 1-2 parts of lubricant, and 0.2-0.5 parts of heat stabilizer.

[0008] In the technical solution disclosed in the present invention, low-density polyethylene resin is used as the matrix material to provide basic electrical insulation performance and flexibility while ensuring the processability of the material. The number of parts of low-density polyethylene resin can be selected from 80 parts, 82 parts, 84 parts, 85 parts, 86 parts, 88 parts, 90 parts, 92 parts, 94 parts, 95 parts, 96 parts, 98 parts, and 100 parts, but is not limited to the listed values. Other values ​​not listed within the numerical range are also applicable.

[0009] In the technical solution disclosed in the present invention, the tensile strength of the material is improved by adding nylon. At the same time, the inherent high crystallinity of nylon gives the material excellent heat deformation resistance, inhibiting softening and creep phenomena in high temperature environments. The number of nylon parts can be selected as 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, and 15 parts, but is not limited to the listed values. Other values ​​not listed within the numerical range are also applicable.

[0010] In the technical solution disclosed in the present invention, the preparation method of the composite flame retardant is as follows:

[0011] S1. Preparation of the complex

[0012] Aluminum salt and expandable graphite are ultrasonically dispersed in deionized water, and then ammonia water is added thereto, heated and stirred for reaction, and after the reaction is completed, the composite is obtained by centrifugation and drying.

[0013] In this step, the mass ratio of the aluminum salt, expandable graphite and ammonia water is 4-8:10-15:25-40.

[0014] In this step, the aluminum salt is selected from soluble aluminum salts, for example, aluminum chloride, aluminum nitrate and aluminum sulfate.

[0015] In this step, the mass fraction of the ammonia water is 25-30%.

[0016] In this step, the temperature of the heating and stirring reaction is 60-80°C, for example, 60°C, 65°C, 70°C, 75°C, or 80°C can be selected; the time of the heating and stirring reaction is 2-4h, for example, 2h, 2.5h, 3h, 3.5h, or 4h can be selected, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0017] In this step, aluminum hydroxide is loaded on expandable graphite, which expands when exposed to high temperature to form a worm-like carbon layer. The aluminum hydroxide absorbs heat and decomposes to generate aluminum oxide and releases water vapor. The aluminum oxide particles fill the pores of the expanded carbon layer to form a dense barrier. The water vapor dilutes the concentration of the combustible gas, thereby improving the flame retardant properties of the material.

[0018] S2. Preparation of epoxy grafted composite

[0019] The composite is ultrasonically dispersed in an ethanol aqueous solution, and then γ-glycidyloxypropyltrimethoxysilane is added thereto, and the mixture is stirred for reaction. After the reaction is completed, the mixture is centrifuged, washed, and dried to obtain an epoxy-grafted composite.

[0020] In this step, the mass ratio of the composite to γ-glycidyloxypropyltrimethoxysilane is 10-15:2-4, for example, 10:2, 10:3, 10:4, 12:2, 12:3, 12:4, 15:2, 15:3, 15:4 can be selected, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0021] In this step, the surface of the composite is treated with γ-glycidyloxypropyltrimethoxysilane to introduce epoxy groups onto the surface of the composite, thereby facilitating subsequent reactions.

[0022] S3. Preparation of organic complex

[0023] The epoxy grafted complex is dispersed in an organic solvent, and then 2-vinyl-4,6-diamino-1,3,5-triazine and triethylamine are added thereto, and the mixture is heated for reaction. After the reaction is completed, the mixture is filtered, washed, and dried to obtain an organic complex.

[0024] In this step, the mass ratio of the epoxy grafted complex, 2-vinyl-4,6-diamino-1,3,5-triazine and triethylamine is 10-15:4-8:5-10. In some embodiments of the present invention, for example, 10:4:5, 10:6:8, 10:8:10, 12:4:5, 12:6:8, 12:8:10, 15:6:8, and 15:8:10 can be selected, but the ratio is not limited to the listed values. Other values ​​not listed within the numerical range are also applicable.

[0025] In this step, the heating reaction temperature is 65-85°C, for example, 65°C, 70°C, 75°C, 80°C, or 85°C can be selected; the heating and stirring reaction time is 2-4h, for example, 2h, 2.5h, 3h, 3.5h, or 4h can be selected, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0026] In this step, under the action of the catalyst triethylamine, the epoxy group in the epoxy grafted composite reacts with the amino group in 2-vinyl-4,6-diamino-1,3,5-triazine, introducing the vinyl group and the triazine group into the composite. The triazine group can not only improve the material's resistance to ultraviolet aging, but also form a carbonized layer at high temperature, further improving the material's flame retardant properties.

[0027] S4. Preparation of composite flame retardant

[0028] The organic compound is dispersed in a toluene solvent, and then vinyl silicone oil, styrene and benzoyl peroxide are added thereto, and heated to react. After the reaction is completed, the compound flame retardant is obtained by filtering, washing and drying.

[0029] In this step, the mass ratio of the organic compound, vinyl silicone oil, styrene and benzoyl peroxide is 10-15:3-6:3-6:0.1-0.2.

[0030] In this step, the heating reaction temperature is 60-90°C, for example, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, and 90°C can be selected; the heating reaction time is 3-5h, for example, 3h, 3.5h, 4h, 4.5h, and 5h can be selected, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0031] In this step, under the action of the initiator benzoyl peroxide, vinyl silicone oil and styrene copolymerize to form a styrene-silicone copolymer, which is grafted onto the organic composite. The siloxane segments in the styrene-silicone copolymer are hydrophobic and can block the penetration of water molecules. The rigid benzene ring structure in the styrene-silicone copolymer has heat aging resistance. By forming the styrene-silicone copolymer on the surface of the organic composite, the material's resistance to wet heat aging is improved. At the same time, the flexible siloxane segments and the rigid benzene ring structure are anchored in the resin matrix to form a chemical bridging structure, thereby enhancing the material's mechanical properties.

[0032] In the technical solution disclosed in the present invention, the compatibilizer is selected from maleic anhydride grafted polyethylene or ethylene-vinyl acetate copolymer, and the number of parts of the compatibilizer can be selected from 8 parts, 9 parts, 10 parts, 11 parts, and 12 parts, but is not limited to the listed values. Other values ​​not listed within the numerical range are also applicable.

[0033] In the technical solution disclosed in the present invention, the antioxidant is selected from antioxidant 1010 or antioxidant 1076, and the number of parts of the antioxidant can be selected from 2 parts, 2.5 parts, 3 parts, 3.5 parts, and 4 parts, but is not limited to the listed values. Other values ​​not listed within the numerical range are also applicable.

[0034] In the technical solution disclosed in the present invention, the lubricant is selected from at least one of calcium stearate, polyethylene wax, stearic acid, and stearic acid monoglyceride. The number of parts of the lubricant can be selected from 1 part, 1.2 parts, 1.5 parts, 1.6 parts, 1.8 parts, 1.9 parts, and 2 parts, but is not limited to the listed values. Other values ​​not listed within the numerical range are also applicable.

[0035] In the technical solution disclosed in the present invention, the heat stabilizer is selected from calcium zinc heat stabilizer CZ-113 or calcium zinc heat stabilizer CZ-116, and the amount of the heat stabilizer can be selected from 0.2 parts, 0.3 parts, 0.4 parts, and 0.5 parts, but is not limited to the listed values. Other values ​​not listed within the numerical range are also applicable.

[0036] The present invention also provides a method for preparing the flame retardant and fireproof cable material, comprising the following steps:

[0037] Low-density polyethylene resin, nylon, composite flame retardant, compatibilizer, antioxidant, lubricant and heat stabilizer are added to a high-speed mixer according to the formula amount, mixed evenly to obtain a mixture, and then the mixture is added to a twin-screw extruder for extrusion and granulation to obtain a flame-retardant and fire-proof cable material.

[0038] Compared with the prior art, the present invention has the following beneficial effects:

[0039] (1) The flame-retardant and fire-proof cable material provided by the present invention adopts low-density polyethylene resin as a matrix material to provide basic electrical insulation performance and flexibility while ensuring the processability of the material; by adding nylon to the raw materials, the tensile strength of the material is improved, and by performing multi-step treatment on the expandable graphite, the technical problems of poor dispersibility and easy migration failure of traditional inorganic fillers are improved. The flame-retardant and fire-proof cable material prepared by the present invention has excellent mechanical properties, flame retardant properties and aging resistance, ensuring the structural stability and service life of the cable material in long-term harsh outdoor environments.

[0040] (2) The present invention loads aluminum hydroxide on expandable graphite. When the expandable graphite is exposed to high temperature, it expands to form a worm-like carbon layer. The aluminum hydroxide absorbs heat and decomposes to generate aluminum oxide and releases water vapor. The aluminum oxide particles fill the pores of the expanded carbon layer to form a dense barrier. At the same time, the water vapor dilutes the concentration of the combustible gas, thereby improving the flame retardant properties of the material.

[0041] (3) The present invention improves the material's resistance to ultraviolet aging by grafting 2-vinyl-4,6-diamino-1,3,5-triazine onto the composite and introducing a triazine group. At the same time, the triazine group can also form a carbonized layer at high temperature, further improving the material's flame retardant properties. Subsequently, a styrene-silicone copolymer is grafted onto the organic composite. The siloxane chain segments in the styrene-silicone copolymer are hydrophobic and can block the penetration of water molecules. The rigid benzene ring structure in the styrene-silicone copolymer has heat aging resistance. By forming a styrene-silicone copolymer on the surface of the organic composite, the material's resistance to wet heat aging is improved. At the same time, the flexible siloxane chain segments and the rigid benzene ring structure are anchored in the resin matrix to form a chemical bridging structure, thereby enhancing the material's mechanical properties. DETAILED DESCRIPTION

[0042] The present invention is further described in detail below through specific preferred embodiments, but the present invention is not limited to the following embodiments.

[0043] It should be noted that, unless otherwise specified, all chemical reagents involved in the present invention were purchased through commercial channels.

[0044] The low-density polyethylene resin used in the embodiments of the present invention is produced by Mitsui Chemicals of Japan, with the brand name L2100; the brand name of nylon 6 is BC304; the mesh size of the expandable graphite is 200 mesh; the CAS number of the vinyl silicone oil is 26710-23-6; and the compatibilizer is maleic anhydride grafted polyethylene, purchased from Dongguan Nabaichuan Plastics Co., Ltd.

[0045] Example 1

[0046] A method for preparing a flame retardant and fireproof cable material comprises the following steps:

[0047] 80 parts of low-density polyethylene resin, 10 parts of nylon 6, 15 parts of composite flame retardant, 8 parts of maleic anhydride grafted polyethylene, 2 parts of antioxidant 1076, 1 part of stearic acid and 0.2 parts of calcium zinc heat stabilizer CZ-113 are added to a high-speed mixer and mixed evenly to obtain a mixture. The mixture is then added to a twin-screw extruder and extruded and granulated at 235°C to obtain a flame-retardant and fire-resistant cable material.

[0048] The preparation method of the composite flame retardant is as follows:

[0049] S1. Ultrasonic dispersion of 4 g of aluminum nitrate and 10 g of expandable graphite in 150 mL of deionized water was followed by addition of 25 g of 25 wt% aqueous ammonia. The mixture was heated and stirred at 60° C. for 4 h. After the reaction was complete, the mixture was centrifuged and dried to obtain a composite.

[0050] S2. Ultrasonic dispersion of 10 g of the composite in 100 mL of ethanol-water solution (volume ratio of ethanol to water is 4:1) was performed, followed by addition of 2 g of γ-glycidyloxypropyltrimethoxysilane, and the mixture was stirred at room temperature for 2 h. After the reaction was completed, the mixture was centrifuged, washed, and dried to obtain an epoxy-grafted composite.

[0051] S3, dispersing 10 g of the epoxy-grafted complex in 100 mL of an organic solvent, DMF, and then adding 4 g of 2-vinyl-4,6-diamino-1,3,5-triazine and 5 g of triethylamine, heating the mixture at 80° C. for 3 h. After the reaction is completed, filtering, washing, and drying the mixture to obtain an organic complex;

[0052] S4. Disperse 10 g of the organic compound in 100 mL of toluene solvent, then add 3 g of vinyl silicone oil, 3 g of styrene and 0.1 g of benzoyl peroxide, and heat to react at 70°C for 4 h. After the reaction is completed, filter, wash and dry to obtain a composite flame retardant.

[0053] Example 2

[0054] A method for preparing a flame retardant and fireproof cable material comprises the following steps:

[0055] 100 parts of low-density polyethylene resin, 15 parts of nylon 6, 25 parts of composite flame retardant, 12 parts of maleic anhydride grafted polyethylene, 4 parts of antioxidant 1076, 2 parts of stearic acid and 0.5 parts of calcium zinc heat stabilizer CZ-113 are added to a high-speed mixer and mixed evenly to obtain a mixture. The mixture is then added to a twin-screw extruder and extruded and granulated at 235°C to obtain a flame-retardant and fire-resistant cable material.

[0056] The preparation method of the composite flame retardant is as follows:

[0057] S1. Ultrasonic dispersion of 8 g of aluminum nitrate and 15 g of expandable graphite in 150 mL of deionized water was performed, followed by addition of 40 g of 25 wt% aqueous ammonia, and the mixture was heated and stirred at 60° C. for 4 h. After the reaction was complete, the mixture was centrifuged and dried to obtain a composite.

[0058] S2. Ultrasonic dispersion of 15 g of the composite in 100 mL of ethanol-water solution (volume ratio of ethanol to water is 4:1) was performed, followed by addition of 4 g of γ-glycidyloxypropyltrimethoxysilane, and the mixture was stirred at room temperature for 2 h. After the reaction was completed, the mixture was centrifuged, washed, and dried to obtain an epoxy-grafted composite.

[0059] S3, dispersing 15 g of the epoxy-grafted complex in 100 mL of an organic solvent, DMF, and then adding 8 g of 2-vinyl-4,6-diamino-1,3,5-triazine and 10 g of triethylamine, heating the mixture at 80° C. for 3 h. After the reaction is completed, filtering, washing, and drying the mixture to obtain an organic complex;

[0060] S4. Disperse 15 g of the organic compound in 100 mL of toluene solvent, then add 6 g of vinyl silicone oil, 6 g of styrene and 0.2 g of benzoyl peroxide, and heat to react at 70°C for 4 h. After the reaction is completed, filter, wash and dry to obtain a composite flame retardant.

[0061] Example 3

[0062] A method for preparing a flame retardant and fireproof cable material comprises the following steps:

[0063] 85 parts of low-density polyethylene resin, 12 parts of nylon 6, 20 parts of composite flame retardant, 10 parts of maleic anhydride grafted polyethylene, 3 parts of antioxidant 1076, 1 part of stearic acid and 0.4 parts of calcium zinc heat stabilizer CZ-113 are added to a high-speed mixer and mixed evenly to obtain a mixture, which is then added to a twin-screw extruder and extruded and granulated at 235°C to obtain a flame-retardant and fire-resistant cable material.

[0064] The preparation method of the composite flame retardant is as follows:

[0065] S1. Ultrasonic dispersion of 6 g of aluminum nitrate and 12 g of expandable graphite in 150 mL of deionized water was performed, followed by addition of 30 g of 25 wt% aqueous ammonia, and the mixture was heated and stirred at 70° C. for 3 h. After the reaction was complete, the mixture was centrifuged and dried to obtain a composite.

[0066] S2. Ultrasonic dispersion of 12 g of the composite in 100 mL of ethanol-water solution (volume ratio of ethanol to water is 4:1) was followed by addition of 3 g of γ-glycidyloxypropyltrimethoxysilane. The mixture was stirred at room temperature for 2 h. After the reaction was completed, the mixture was centrifuged, washed, and dried to obtain an epoxy-grafted composite.

[0067] S3, dispersing 12 g of the epoxy-grafted complex in 100 mL of an organic solvent, DMF, and then adding 6 g of 2-vinyl-4,6-diamino-1,3,5-triazine and 8 g of triethylamine, heating the mixture at 80° C. for 3 h. After the reaction is complete, filtering, washing, and drying the mixture to obtain an organic complex;

[0068] S4. Disperse 12 g of the organic compound in 100 mL of toluene solvent, then add 4 g of vinyl silicone oil, 5 g of styrene and 0.2 g of benzoyl peroxide, and heat to react at 70°C for 4 h. After the reaction is completed, filter, wash and dry to obtain a composite flame retardant.

[0069] Comparative Example 1

[0070] A method for preparing a flame retardant and fireproof cable material comprises the following steps:

[0071] 80 parts of low-density polyethylene resin, 10 parts of nylon 6, 15 parts of composite flame retardant, 8 parts of maleic anhydride grafted polyethylene, 2 parts of antioxidant 1076, 1 part of stearic acid and 0.2 parts of calcium zinc heat stabilizer CZ-113 are added to a high-speed mixer and mixed evenly to obtain a mixture. The mixture is then added to a twin-screw extruder and extruded and granulated at 235°C to obtain a flame-retardant and fire-resistant cable material.

[0072] The preparation method of the composite flame retardant is as follows:

[0073] S1, 10g of expandable graphite was ultrasonically dispersed in 100mL of ethanol and water (the volume ratio of ethanol to water was 4:1), and then 2g of γ-glycidyloxypropyltrimethoxysilane was added thereto, and the mixture was stirred at room temperature for 2h. After the reaction was completed, the mixture was centrifuged, washed, and dried to obtain epoxy-grafted expandable graphite;

[0074] S2, dispersing 10 g of epoxy-grafted expandable graphite in 100 mL of an organic solvent, DMF, and then adding 4 g of 2-vinyl-4,6-diamino-1,3,5-triazine and 5 g of triethylamine thereto, heating the mixture at 80° C. for 3 h, and after the reaction is completed, filtering, washing, and drying to obtain an organic complex;

[0075] S3. Disperse 10 g of the organic compound in 100 mL of toluene solvent, then add 3 g of vinyl silicone oil, 3 g of styrene and 0.1 g of benzoyl peroxide, and heat to react at 70°C for 4 h. After the reaction is completed, filter, wash and dry to obtain a composite flame retardant.

[0076] Compared with Example 1, Comparative Example 1 does not perform aluminum hydroxide loading treatment on the expandable graphite.

[0077] Comparative Example 2

[0078] A method for preparing a flame retardant and fireproof cable material comprises the following steps:

[0079] 80 parts of low-density polyethylene resin, 10 parts of nylon 6, 15 parts of composite flame retardant, 8 parts of maleic anhydride grafted polyethylene, 2 parts of antioxidant 1076, 1 part of stearic acid and 0.2 parts of calcium zinc heat stabilizer CZ-113 are added to a high-speed mixer and mixed evenly to obtain a mixture. The mixture is then added to a twin-screw extruder and extruded and granulated at 235°C to obtain a flame-retardant and fire-resistant cable material.

[0080] The preparation method of the composite flame retardant is as follows:

[0081] 4 g of aluminum nitrate and 10 g of expandable graphite were ultrasonically dispersed in 150 mL of deionized water, and then 25 g of 25 wt% ammonia water was added thereto. The mixture was heated and stirred at 60° C. for 4 h. After the reaction was completed, the mixture was centrifuged and dried to obtain a composite flame retardant.

[0082] Compared with Example 1, in Comparative Example 2, aluminum hydroxide loading treatment was performed only on the expandable graphite.

[0083] Comparative Example 3

[0084] A method for preparing a flame retardant and fireproof cable material comprises the following steps:

[0085] 80 parts of low-density polyethylene resin, 10 parts of nylon 6, 15 parts of composite flame retardant, 8 parts of maleic anhydride grafted polyethylene, 2 parts of antioxidant 1076, 1 part of stearic acid and 0.2 parts of calcium zinc heat stabilizer CZ-113 are added to a high-speed mixer and mixed evenly to obtain a mixture. The mixture is then added to a twin-screw extruder and extruded and granulated at 235°C to obtain a flame-retardant and fire-resistant cable material.

[0086] The preparation method of the composite flame retardant is as follows:

[0087] S1. Ultrasonic dispersion of 4 g of aluminum nitrate and 10 g of expandable graphite in 150 mL of deionized water was followed by addition of 25 g of 25 wt% aqueous ammonia. The mixture was heated and stirred at 60° C. for 4 h. After the reaction was complete, the mixture was centrifuged and dried to obtain a composite.

[0088] S2. Ultrasonic dispersion of 10 g of the composite in 100 mL of ethanol-water solution (volume ratio of ethanol to water is 4:1) was performed, followed by addition of 2 g of γ-glycidyloxypropyltrimethoxysilane, and the mixture was stirred at room temperature for 2 h. After the reaction was completed, the mixture was centrifuged, washed, and dried to obtain an epoxy-grafted composite.

[0089] S3, dispersing 10 g of the epoxy-grafted complex in 100 mL of an organic solvent, DMF, and then adding 4 g of 2-vinyl-4,6-diamino-1,3,5-triazine and 5 g of triethylamine, heating the mixture at 80° C. for 3 h. After the reaction is completed, filtering, washing, and drying the mixture to obtain an organic complex;

[0090] S4. Disperse 10 g of the organic complex in 100 mL of toluene solvent, then add 3 g of styrene and 0.1 g of benzoyl peroxide, and heat to react at 70° C. for 4 h. After the reaction is completed, filter, wash, and dry to obtain a composite flame retardant.

[0091] Compared with Example 1, in Comparative Example 3, no vinyl silicone oil was added in step S4.

[0092] Comparative Example 4

[0093] A method for preparing a flame retardant and fireproof cable material comprises the following steps:

[0094] 80 parts of low-density polyethylene resin, 10 parts of nylon 6, 15 parts of composite flame retardant, 8 parts of maleic anhydride grafted polyethylene, 2 parts of antioxidant 1076, 1 part of stearic acid and 0.2 parts of calcium zinc heat stabilizer CZ-113 are added to a high-speed mixer and mixed evenly to obtain a mixture. The mixture is then added to a twin-screw extruder and extruded and granulated at 235°C to obtain a flame-retardant and fire-resistant cable material.

[0095] The preparation method of the composite flame retardant is as follows:

[0096] S1. Ultrasonic dispersion of 4 g of aluminum nitrate and 10 g of expandable graphite in 150 mL of deionized water was followed by addition of 25 g of 25 wt% aqueous ammonia. The mixture was heated and stirred at 60° C. for 4 h. After the reaction was complete, the mixture was centrifuged and dried to obtain a composite.

[0097] S2. Ultrasonic dispersion of 10 g of the composite in 100 mL of ethanol-water solution (volume ratio of ethanol to water is 4:1) was performed, followed by addition of 2 g of γ-glycidyloxypropyltrimethoxysilane, and the mixture was stirred at room temperature for 2 h. After the reaction was completed, the mixture was centrifuged, washed, and dried to obtain an epoxy-grafted composite.

[0098] S3, dispersing 10 g of the epoxy-grafted complex in 100 mL of an organic solvent, DMF, and then adding 4 g of 2-vinyl-4,6-diamino-1,3,5-triazine and 5 g of triethylamine, heating the mixture at 80° C. for 3 h. After the reaction is completed, filtering, washing, and drying the mixture to obtain an organic complex;

[0099] S4. Disperse 10 g of the organic complex in 100 mL of toluene solvent, then add 3 g of vinyl silicone oil and 0.1 g of benzoyl peroxide, and heat to react at 70° C. for 4 h. After the reaction is completed, filter, wash, and dry to obtain a composite flame retardant.

[0100] Compared with Example 1, in Comparative Example 4, no styrene was added in step S4.

[0101] The materials prepared in Examples 1-3 and Comparative Examples 1-4 were prepared into samples that met the test standards, and then performance tests were performed, as follows:

[0102] Flame retardant performance test: The test was conducted according to the standard GB / T 2406.2-2009 "Plastics - Determination of Combustion Behavior by Oxygen Index Method - Part 2: Room Temperature Test". The test was repeated three times and the results were averaged.

[0103] Tensile strength and elongation at break test: Tested according to GB / T 2951.11-2008 "General test methods for insulation and sheathing materials of electric and optical cables - Part 11: General test methods - Thickness and dimensional measurements - Mechanical properties tests", tested three times and the results were averaged;

[0104] Moisture-heat aging resistance test: The test was conducted according to the standard GB / T 2423.40-2013 "Environmental testing Part 2: Test method Test Cx: Unsaturated high-pressure steam steady state wet heat", with a temperature of 120°C and a relative humidity of 85% for 48 hours, and the tensile strength retention was tested;

[0105] UV aging resistance test: Tested according to Method A in GB / T 16422.3-2022, with an irradiation time of 30 days, and the tensile strength retention rate was tested;

[0106] The test results are shown in Table 1.

[0107] Table 1 Performance test results

[0108]

[0109] Finally, it should be noted that the above embodiments do not limit the present invention in any form. Those skilled in the art will appreciate that modifications and improvements can be made based on the present invention. Therefore, any modifications or improvements made without departing from the spirit of the present invention are intended to fall within the scope of protection claimed in the present invention.

Claims

1. A flame retardant and fireproof cable material, characterized in that: The raw materials include the following components in parts by weight: 80-100 parts of low-density polyethylene resin, 10-15 parts of nylon, 15-25 parts of composite flame retardant, 8-12 parts of compatibilizer, 2-4 parts of antioxidant, 1-2 parts of lubricant, and 0.2-0.5 parts of heat stabilizer.

2. The flame retardant and fireproof cable material according to claim 1, characterized in that: The preparation method of the composite flame retardant is as follows: S1. Ultrasonic dispersion of aluminum salt and expandable graphite in deionized water, followed by addition of aqueous ammonia, heating and stirring for reaction, and after completion of the reaction, centrifugation and drying to obtain a composite; S2, ultrasonically dispersing the composite in an ethanol aqueous solution, then adding γ-glycidyloxypropyltrimethoxysilane thereto, stirring for reaction, and after the reaction is completed, centrifuging, washing, and drying to obtain an epoxy-grafted composite; S3, dispersing the epoxy-grafted complex in an organic solvent, then adding 2-vinyl-4,6-diamino-1,3,5-triazine and triethylamine thereto, heating for reaction, and filtering, washing, and drying after the reaction is complete to obtain an organic complex; S4. Dispersing the organic compound in a toluene solvent, then adding vinyl silicone oil, styrene and benzoyl peroxide thereto, heating for reaction, and after the reaction is completed, filtering, washing and drying to obtain a composite flame retardant.

3. The flame retardant and fireproof cable material according to claim 2, characterized in that: In step S1, the mass ratio of the aluminum salt, expandable graphite and ammonia water is 4-8:10-15:25-40.

4. The flame retardant and fireproof cable material according to claim 2, characterized in that: In step S1, the temperature for the heating and stirring reaction is 60-80° C., and the time for the heating and stirring reaction is 2-4 h.

5. The flame retardant and fireproof cable material according to claim 2, characterized in that: In step S2, the mass ratio of the composite to γ-glycidyloxypropyltrimethoxysilane is 10-15:2-4.

6. The flame retardant and fireproof cable material according to claim 2, characterized in that: In step S3, the mass ratio of the epoxy grafted compound, 2-vinyl-4,6-diamino-1,3,5-triazine and triethylamine is 10-15:4-8:5-10.

7. The flame retardant and fireproof cable material according to claim 2, characterized in that: In step S4, the mass ratio of the organic compound, vinyl silicone oil, styrene and benzoyl peroxide is 10-15:3-6:3-6:0.1-0.

2.

8. The flame retardant and fireproof cable material according to claim 1, characterized in that: The compatibilizer is selected from maleic anhydride grafted polyethylene or ethylene-vinyl acetate copolymer, and the antioxidant is selected from antioxidant 1010 or antioxidant 1076.

9. The flame retardant and fireproof cable material according to claim 1, characterized in that: The lubricant is selected from at least one of calcium stearate, polyethylene wax, stearic acid, and stearic acid monoglyceride, and the heat stabilizer is selected from calcium zinc heat stabilizer CZ-113 or calcium zinc heat stabilizer CZ-116.

10. The method for preparing the flame retardant and fireproof cable material according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: adding low-density polyethylene resin, nylon, composite flame retardant, compatibilizer, antioxidant, lubricant and heat stabilizer into a high-speed mixer according to the formula amount, mixing evenly to obtain a mixture, and then adding the mixture into a twin-screw extruder for extrusion and granulation to obtain the flame-retardant and fireproof cable material.

Citation Information

Patent Citations

  • PVC (polyvinyl chloride) cable material with flame retardant property and preparation method thereof

    CN115948005A

Cited By

  • Flame-retardant fireproof cable and preparation method thereof

    CN122011557A